A Case of Langerhans Cell Histiocytosis Presenting with Suprasellar Mass and Panhypopituitarism Clinic - Emek Topuz; Dilek Tüzün; Nursel Yurttutan; Murat Şahin (Endocrinology Research and Practice)
Langerhans cell histiocytosis (LCH) is a rare disease involving multiple systems, and it is caused by excessive proliferation of Langerhans cells. The hypothalamic-pituitary region (HPR) is involved in 5%-50% of all LCH patients, particularly those with multifocal disease. Diabetes insipidus (DI), the most common endocrinal abnormality, occurs in 15%-50% of patients with HPR-LCH. Anterior pituitary deficiency occurs in the minority, in 5%-20% of the patients, usually in combination with DI. The disease is clinically heterogeneous. The most commonly involved organs are the skeleton (78.7%) and skin (36.7%). Involvement of multiple organs such as the skin, lymph nodes, lungs, spleen, liver, bone marrow, ear, nose, and throat is a criterion for poor prognosis. We report a 19-year-old woman who presented with a pituitary suprasellar mass, had anterior pituitary deficiency (APD) but no DI at the time of diagnosis, and had the ear and mastoid bone involvement. We initially did not consider LCH but diagnosed it later. In the literature, we found only 2 cases with APD but without DI among patients with an LCH diagnosis. The clinical features of HPR-LCH are similar to other hypothalamicpituitary disorders; thus, differential diagnosis is necessary. Accurate and rapid diagnosis is crucial for HPR-LCH; its symptoms are progressive and irreversible. Unlike other disorders of HPR, LCH is treated with chemotherapy. Necessary surgical interventions must be performed to make a rapid pathologic diagnosis.